2021
DOI: 10.1038/s41598-021-83982-8
|View full text |Cite
|
Sign up to set email alerts
|

Mammillary body atrophy and other MRI correlates of school-age outcome following neonatal hypoxic-ischemic encephalopathy

Abstract: The mammillary bodies (MB) and hippocampi are important for memory function and are often affected following neonatal hypoxic ischemic encephalopathy (HIE). The aim of this study was to assess neurodevelopmental outcome in 10-year-old children with HIE with and without therapeutic hypothermia. Additional aims were to assess the associations between MB atrophy, brain volumes (including the hippocampi), white matter microstructure and neurodevelopmental outcome at school-age. Ten-year-old children with HIE were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…Furthermore, our data showing higher rates of abnormalities of the MBs among infants with hypoglycemia, and worse VIQ scores in hypoglycemic infants with abnormal MBs, suggest that these infants are at increased risk for neurocognitive impairments later in life, as a recent study has reported a strong association between MB atrophy with episodic memory and neurocognitive outcome at 10 years of age. [17] These findings all strongly support continued 0-po9neurodevelopmental follow-up beyond 24 months of age. Infants with hypoglycemia had higher lactate levels on admission, possibly due to a higher rate of anaerobic glycolysis.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 53%
See 2 more Smart Citations
“…Furthermore, our data showing higher rates of abnormalities of the MBs among infants with hypoglycemia, and worse VIQ scores in hypoglycemic infants with abnormal MBs, suggest that these infants are at increased risk for neurocognitive impairments later in life, as a recent study has reported a strong association between MB atrophy with episodic memory and neurocognitive outcome at 10 years of age. [17] These findings all strongly support continued 0-po9neurodevelopmental follow-up beyond 24 months of age. Infants with hypoglycemia had higher lactate levels on admission, possibly due to a higher rate of anaerobic glycolysis.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 53%
“…previously. [16][17][18][19][20][21][22][23][24] Indications for TH have been described before and were not changed during the study period. [25] Infants with a postnatal collapse (sudden cardiovascular collapse after birth in infants initially considered healthy), congenital malformations, central nervous system infections or genetic or metabolic disorders were excluded to explore the incidence of hypoglycemia.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study across multiple centers, it was demonstrated that approximately 40% of infants with HIE who had received hypothermia had signal abnormalities in the MBs [45]. Annink et al reported that MB atrophy was significantly associated with lower intelligence quotients, verbal long-term memory scores, and visualspatial long-term memory scores at 10 years of age [46]. Some infants with HIE demonstrate brain injury in the limbic system, particularly in the hippocampal region, which can lead to long-term episodic memory impairment at school age [42,43].…”
Section: Other Injury Associated With Hiementioning
confidence: 99%
“…Lesions of the brainstem have also been reported in NE, and are associated with the most severe outcomes (14) with speech, language and communication problems commonly seen in infants with these types of lesions. In infants with NE, reduced volumes of the hippocampus has been identified (39) and is associated with visuospatial memory at 9-10 years of age (40), and injury to the hippocampus has been associated with neurocognition and memory at schoolage in NE (41). The cerebellum which is also important for language functioning (42) ( is increasingly being identified as a brain region vulnerable to hypoxia in infants with NE (43), and in preterm infants, cerebellar abnormalities have been associated with neurodevelopmental outcomes (44).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%